PENGGAMBARAN MAKROFAUNA DAN MESOFAUNA TANAH DIBAWAH TEGAKAN KARET (HEVEA BRAZILLIENSIS) DI LAHAN GAMBUT - Risman Risman; Al ikhsan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the diversity of macrofauna and mesofauna peat soil macrofauna calculate population density and mesofauna peat soil between plants and close rubber plant (Hevea Brazilliensis),Research conducted in the community rubber plantations, pineapple Kualu Village, District Mines Kampar. The type of soil used was Peat. The research was conducted over three months starting from March to May 2016. The study was conducted by survey sampling for macrofauna and mesofauna ground observations determined by purposive sampling method, extensive research sites 1 360 hectares with a population of crop plants, for research taken 5%, namely 18 plants, plant determination random sample of observations made, the observed data diverse population and relative density of macrofauna and mesofauna analyzed by descriptive statistics. The results showed the soil macrofauna and mesofauna among plants have more than the number of close plant, Keywords: Macrofauna, mesofauna, peat